Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Pendidikan Anak Usia Dini di TK Kecamatan Siborongborong T.A 2024/2025 - Fery Refmil Hutasoit (Institut Nalanda, 2024)
The problem in this study is the role of principal leadership in improving teacher performance, it needs to be understood that every leader is responsible for directing what is good for teachers. The principal is the highest leader in an educational institution who is responsible for everything related to the smooth running of the school in order to realize the goals of the school. The principal always encourages teachers to carry out their duties well and the higher the intensity of the principal's leadership towards teachers, the higher the level of teacher performance in carrying out their work. This indicates that the behavior of the leader has brought significant changes in improving teacher performance, is able to bring a sense of self-confidence to teachers, is able to provide new ideas to teachers so that they are able to communicate well, is able to provide inspiration for school progress, is able to provide personal attention to all teachers. The purpose of this research is to determine the influence of the principal's leadership on teacher performance in kindergartens in Siborongborong District, Kab. North Tapanuli T.A 2024/2025. The method used in this research is a quantitative research method which is ex-post facto. The population is 30 Siborongborong Kindergarten teachers for the 2023/2024 academic year and this research is population research. Data was collected using a closed questionnaire with 34 items. The results of data analysis show that the principal's leadership has a positive and significant influence on the performance of early childhood education teachers at Siborongborong Kindergarten, proven through the following data analysis: 1) Test of analysis requirements: a) positive relationship test obtained by rxy = 0,718 > rtabel(=0,05,n=30) = 0,361 Thus it is known that there is a positive relationship between variable X and variable Y. b) a significant relationship test was obtained thitung= 5,464 > ttabel(=0,05,dk=n-2=28)= 2,048 Thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained the regression equation Y ̂=